Exploring Teachers' Digital Pedagogical Competency and Its Effect on Learning Outcomes in Rural and Urban Schools - Moh. Imron Rosidi; Mu'tasim Fikri; Tanveer Shah (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the relationship between teachers' digital pedagogical competency and student learning outcomes in both rural and urban schools. A descriptive survey design, utilizing correlational and regression analyses, was employed to examine this relationship. Data were collected from teachers using a structured questionnaire assessing their digital competence, while student learning outcomes were measured through academic performance records. The results revealed significant differences between urban and rural schools in terms of teachers’ digital competence, with urban teachers demonstrating higher levels of digital skills. A positive correlation was found between teachers' digital competence and student learning outcomes, particularly in urban schools, where digital tools were more readily available. The regression analysis further confirmed that digital competence was a significant predictor of student achievement, with urban schools outperforming rural ones even after controlling for teacher experience. The study suggests that infrastructure availability, teacher training, and institutional support play crucial roles in enhancing digital competence, particularly in rural schools, where such resources are often limited. These findings underscore the need for policy reforms that ensure equitable access to digital tools and professional development opportunities for teachers across both rural and urban settings. Recommendations include targeted interventions for rural schools to bridge the digital divide and improve student learning outcomes through enhanced teacher digital competencies.